(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the intricate processes of vocabulary classification and word formation within the lexicology of the Russian language. It examines various methods of categorizing vocabulary, including classifications by parts of speech, semantic fields, origin, style and register, frequency, and functionality. The study highlights the significance of understanding these classifications in relation to the structure and usage of the language. Additionally, the article delves into the mechanisms of word formation, such as derivation, compounding, and borrowing, illustrating how new words emerge and evolve within the linguistic landscape. By analyzing these processes, the paper aims to provide a comprehensive understanding of the dynamic nature of Russian vocabulary and its implications for language learners, educators, and linguists.